Manganese-zinc power ferrite material as well as preparation method and application thereof

Through the fine adjustment of the appropriate main formula and additives, manganese-zeb power ferrite materials achieve low loss performance in the range of 140-160℃, solving the high loss problem of existing materials under ultra-high temperature conditions, and meeting the high temperature application of electronic devices need.

CN119263805APending Publication Date: 2025-01-07HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310830072.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing manganese-zeb ferrite materials have high power loss at temperatures above 140°C, which cannot meet the needs of electronic devices under ultra-high temperature conditions.

Method used

Through fine-tuning of suitable main formulas and additives, the power consumption valley of manganese-zeb power ferrite material is controlled within the range of 140-160°C. Fe2O3, ZnO, MnO are used as main components, SnO2, CaCO3, Nb2O5 and ZrO2 are used as additives. Suppress electron transitions and form high resistance layers, reducing eddy current and hysteresis losses.

Benefits of technology

The low loss performance of manganese-zeb power ferrite material in the temperature range of 140-160°C is achieved, and the power consumption under 100kHz and 200mT is not exceeding 340kW/m3.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004326694120000111
    Figure BDA0004326694120000111
  • Figure BDA0004326694120000121
    Figure BDA0004326694120000121
Patent Text Reader

Abstract

The invention relates to a manganese-zinc power ferrite material and a preparation method and application thereof, the manganese-zinc power ferrite material comprises main components and additives, the main components comprise Fe2O3, ZnO and MnO; the additive is prepared from SnO2, CaCO3, Nb2O5 and ZrO2. According to the invention, the power consumption valley point is controlled near the working temperature through the proper main formula, and the power consumption valley point of the material is finely adjusted and the power consumption is reduced through the proper additive, so that the manganese-zinc power ferrite material has ultrahigh temperature and low loss performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ferrite manufacturing, and relates to a manganese-zinc power ferrite material and a preparation method and application thereof. Background Art

[0002] With the continuous development of industrial applications, electronic equipment is required to maintain normal operation in extreme environments, so manganese-zinc ferrite is required to have lower losses. At present, the lowest power loss point of most soft magnetic ferrites is between 80 and 140°C. For example, conventional 3C95, 3C97 materials, PC90, PC47 and PC95 materials in the prior art all have the characteristics of high temperature and low power consumption; but these materials are generally used in conventional electronic circuits, and the operating temperature is basically below 140°C, and higher temperature applications are not considered. A typical example is the automated electronic equipment installed in the vicinity of the automobile engine, whose operating temperature can exceed 140°C. Such electronic devices have higher requirements for the high temperature characteristics of ferrites.

[0003] CN 102219486A discloses a high temperature and low loss manganese zinc ferrite material. Although the unit volume loss P is within the temperature range of 120-150°C under the conditions of 100kHz and 200mT, cv All less than 450kW / m 3 , but the minimum loss at 140℃ is still as high as 360kW / m 3 , and no further description is given for losses at temperatures above 140°C.

[0004] CN 113956028A discloses a high temperature and low loss manganese zinc power ferrite and its preparation method. Although its loss is as low as 338kW / m under the conditions of 100kHz, 200mT and 140℃, 3 However, no attention is paid to the loss at temperatures above 140°C. In addition, due to the use of more Co2O3, the production cost is relatively high.

[0005] CN 112125655A discloses a method for preparing high-temperature, high-frequency and low-loss ferrite. Although the power loss is low at a high operating temperature of 120-180° C. in a frequency range of 100-1000 kHz, the loss is still relatively high.

[0006] In summary, it is urgent to provide an ultra-high temperature and low-loss manganese-zinc ferrite with low overall loss in the temperature range of 140 to 160°C to meet the use of electronic devices under ultra-high temperature conditions. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a manganese-zinc power ferrite material and a preparation method and application thereof. The present invention controls the power consumption valley point near the operating temperature through a suitable main formula, and then fine-tunes the power consumption valley point of the material and reduces the power consumption through a suitable additive, so that the manganese-zinc power ferrite material has ultra-high temperature (140-160°C) and low loss (power consumption P under conditions of 100kHz, 200mT). cv ≤340kW / m 3 ) performance.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a manganese-zinc power ferrite material, which includes a main component and an additive, wherein the main component includes Fe2O3, ZnO and MnO; the additive includes SnO2, CaCO3, Nb2O5 and ZrO2.

[0010] The present invention controls the power consumption valley point near the operating temperature through a suitable main formula, and then fine-tunes the power consumption valley point of the material and reduces the power consumption through a suitable additive, so as to realize that the manganese-zinc power ferrite material has ultra-high temperature (140-160°C) and low loss (power consumption P under the conditions of 100kHz and 200mT) cv ≤340kW / m 3 ) performance.

[0011] The additives have the following synergistic effects: by adding SnO2 into the grains, Fe 2+ with Fe 3+ The electron transition between them is used to increase the resistivity inside the grains, thereby reducing eddy current losses; the high resistance layer is formed at the grain boundaries by the combined addition of CaCO3, Nb2O5 and ZrO2 to increase the grain boundary resistivity, while improving the uniformity of the grains and reducing pores, thereby reducing eddy current losses and hysteresis losses.

[0012] Preferably, based on the total amount of the main components as 100 mol%, the main components include:

[0013] Fe2O3 52~52.5mol%

[0014] ZnO 9~11mol%

[0015] MnO balance.

[0016] 52-52.5 mol% of Fe2O3, for example, can be 52 mol%, 52.2 mol%, 52.3 mol%, 52.4 mol% or 52.5 mol%; 9-11 mol% of ZnO, for example, can be 9 mol%, 9.5 mol%, 10 mol%, 10.5 mol% or 11 mol%, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] Preferably, the mass of SnO2 is 1000-2000ppm of the total mass of the main component, for example, it can be 1000ppm, 1200ppm, 1400ppm, 1600ppm, 1800ppm or 2000ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] Preferably, the mass of the CaCO3 is 500 to 1000 ppm of the total mass of the main component, for example, it can be 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm or 1000 ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] Preferably, the mass of the Nb2O5 is 100 to 300 ppm of the total mass of the main component, for example, it can be 100 ppm, 150 ppm, 200 ppm, 250 ppm or 300 ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] Preferably, the mass of ZrO2 is 100 to 300 ppm of the total mass of the main component, for example, it can be 100 ppm, 150 ppm, 200 ppm, 250 ppm or 300 ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] In a second aspect, the present invention provides a method for preparing the manganese-zinc power ferrite material according to the first aspect, the preparation method comprising:

[0022] (1) mixing the main component and SnO2, performing a sand grinding and then pre-burning to obtain a pre-burned material;

[0023] (2) mixing the remaining additives with the obtained pre-burnt material, performing secondary sand grinding and then sintering to obtain the manganese-zinc power ferrite material.

[0024] Mixing SnO2 with the main component is conducive to SnO2 entering the interior of the manganese-zinc ferrite grains, inhibiting electron transitions at high temperatures, increasing the resistivity within the grains, and reducing losses at high temperatures; the combined addition of CaCO3, Nb2O5 and ZrO2 increases the resistivity of the manganese-zinc ferrite grain boundaries, while refining the grains, allowing the grains to grow evenly and reducing total losses.

[0025] Preferably, in the one-time sand milling process described in step (1), the mass ratio of material, ball and water is 1:(5-7):(1-2), for example, it can be 1:5:1, 1:7:1, 1:5:2, 1:7:2 or 1:6:1.5, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] Preferably, the time for the first sanding in step (1) is 2 to 4 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] Preferably, the pre-burning temperature in step (1) is 700-800°C, for example, 700°C, 720°C, 740°C, 760°C, 780°C or 800°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] Preferably, the pre-burning time in step (1) is 2 to 4 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] Preferably, the pre-firing atmosphere in step (1) is an air atmosphere.

[0030] Preferably, during the secondary sand milling in step (2), the mass ratio of material, ball and water is 1:(5-7):(1-2), for example, it can be 1:5:1, 1:7:1, 1:5:2, 1:7:2 or 1:6:1.5, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] Preferably, the time of the secondary sanding in step (2) is 2 to 4 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] Preferably, the average particle size of the sanding material obtained after the secondary sanding in step (2) is 0.9 to 1.2 μm, for example, it can be 0.9 μm, 0.95 μm, 1 μm, 1.1 μm or 1.2 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0033] Preferably, the secondary sand grinding in step (2) further includes granulation and molding.

[0034] Preferably, granulation material is added during the granulation process.

[0035] Preferably, the granulation material comprises PVA and / or PVB.

[0036] Preferably, the mass of the granulated material is 5 to 10 wt% of the mass of the dried powder after secondary sand grinding, for example, it can be 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the sintering in step (2) includes a temperature keeping section and a temperature dropping section.

[0038] Preferably, the insulation period is 150 to 250 minutes, for example, 150 minutes, 180 minutes, 200 minutes, 220 minutes or 250 minutes, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0039] Preferably, the temperature of the insulation section is 1280-1310°C, for example, it can be 1280°C, 1290°C, 1300°C, 1305°C or 1310°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] Preferably, the oxygen content in the cooling section at 1250°C is 3-4 vol%, for example, 3 vol%, 3.2 vol%, 3.4 vol%, 3.6 vol% or 4 vol%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] Preferably, the oxygen content in the cooling section at 1200°C is 2.5-3.5 vol%, for example, it can be 2.5 vol%, 2.8 vol%, 3 vol%, 3.2 vol% or 3.5 vol%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] Preferably, the oxygen content in the cooling section at 1150°C is 1-2 vol%, for example, it can be 1 vol%, 1.2 vol%, 1.4 vol%, 1.6 vol%, 1.8 vol% or 2 vol%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] In the present invention, the oxygen content in the cooling section is controlled and maintained at a relatively high level, thereby enhancing the oxidation of the manganese-zinc ferrite, facilitating the loss valley point of the manganese-zinc ferrite to move toward high temperature, and reducing the loss at high temperature.

[0044] As a preferred technical solution of the preparation method described in the second aspect of the present invention, the preparation method comprises:

[0045] (1) mixing the main component and SnO2, and performing a sand milling for 2 to 4 hours, during which the mass ratio of the material, the ball and the water is 1:(5 to 7):(1 to 2), and then pre-calcining at a temperature of 700 to 800° C. for 2 to 4 hours in an air atmosphere to obtain a pre-calcined material;

[0046] (2) mixing the remaining additives and the obtained pre-sintered material, and performing secondary sand grinding for 2 to 4 hours, during which the mass ratio of the material, the ball and the water is 1:(5 to 7):(1 to 2), and the average particle size of the sand milled material is 0.9 to 1.2 μm, and then mixing 5 to 10 wt% of the dried powder after the secondary sand grinding with PVA and / or PVB for granulation and molding, and finally sintering, the sintering includes a 1280 to 1310° C. insulation stage for 150 to 250 min and a cooling stage, in which the oxygen content at 1250° C. is 3 to 4 vol%, the oxygen content at 1200° C. is 2.5 to 3.5 vol%, and the oxygen content at 1150° C. is 1 to 2 vol%, to obtain the manganese-zinc power ferrite material.

[0047] In a third aspect, the present invention provides an application of the manganese-zinc power ferrite material according to the first aspect, wherein the manganese-zinc power ferrite material is used in electronic devices.

[0048] Compared with the prior art, the present invention has at least the following beneficial effects:

[0049] The present invention controls the power consumption valley point near the operating temperature through a suitable main formula ratio, and then fine-tunes the power consumption valley point of the material and reduces the power consumption through a suitable additive, so as to realize the manganese zinc power ferrite material with ultra-high temperature (140-160°C) and low loss (power consumption P under the conditions of 100kHz and 200mT) cv ≤340kW / m 3 ) performance. DETAILED DESCRIPTION

[0050] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0051] Example 1

[0052] The present embodiment provides a manganese-zinc power ferrite material, which consists of a main component and an additive, wherein the main component is 52 mol% of Fe2O3 and 11 mol% of ZnO, and the rest is MnO; the additive is 1800 ppm of SnO2, 800 ppm of CaCO3, 200 ppm of Nb2O5 and 100 ppm of ZrO2, based on the total mass of the main component.

[0053] The preparation method of the manganese-zinc power ferrite material comprises:

[0054] (1) mixing the main component and SnO2, and performing a sand milling for 3 hours, during which the mass ratio of the material, the ball and the water is 1:6:1.5, and then pre-calcining at a temperature of 750° C. for 3 hours in an air atmosphere after drying to obtain a pre-calcined material;

[0055] (2) Mix the remaining additives and the obtained pre-burnt material, and perform secondary sand grinding for 3 hours. During the process, the mass ratio of material, ball and water is 1:6:1.5, and the average particle size of the sand milled material is 1 μm. Then mix 8wt% of the PVA by mass of the dried powder after secondary sand grinding for granulation and molding, and finally sintering. The sintering includes a 1300°C insulation section for 180min and a cooling section. The oxygen content in the insulation section is 5vol%, and the oxygen content at 1250°C in the cooling section is 3.8vol%, the oxygen content at 1200°C is 3.2vol%, and the oxygen content at 1150°C is 1.8vol%, to obtain the manganese-zinc power ferrite material.

[0056] Example 2

[0057] The present embodiment provides a manganese-zinc power ferrite material, which consists of a main component and an additive, wherein the main component is 52.5 mol% of Fe2O3 and 9 mol% of ZnO, and the rest is MnO; the additive is 1000 ppm of SnO2, 600 ppm of CaCO3, 300 ppm of Nb2O5 and 200 ppm of ZrO2, based on the total mass of the main component.

[0058] The preparation method of the manganese-zinc power ferrite material comprises:

[0059] (1) mixing the main component and SnO2, performing a sand milling for 2 hours, during which the mass ratio of the material, the ball and the water is 1:5:2, and then pre-calcining at a temperature of 700°C for 4 hours in an air atmosphere to obtain a pre-calcined material;

[0060] (2) Mix the remaining additives and the obtained pre-burned material, and perform secondary sand grinding for 4 hours. During the process, the mass ratio of material, ball and water is 1:5:2, and the average particle size of the sand mill is 0.9 μm. Then mix 5 wt% of the PVB of the dried powder after secondary sand grinding for granulation and molding, and finally sintering. The sintering includes a 250 min insulation section at 1280°C and a cooling section. The oxygen content in the insulation section is 5 vol%. In the cooling section, the oxygen content at 1250°C is 3.2 vol%, the oxygen content at 1200°C is 2.6 vol%, and the oxygen content at 1150°C is 1 vol%, to obtain the manganese-zinc power ferrite material.

[0061] Example 3

[0062] The present embodiment provides a manganese-zinc power ferrite material, which consists of a main component and an additive, wherein the main component is 52.1 mol% of Fe2O3 and 9.5 mol% of ZnO, and the rest is MnO; the additive is 1200 ppm of SnO2, 800 ppm of CaCO3, 200 ppm of Nb2O5 and 200 ppm of ZrO2, based on the total mass of the main component.

[0063] The preparation method of the manganese-zinc power ferrite material comprises:

[0064] (1) mixing the main component and SnO2, performing a sand milling for 4 hours, during which the mass ratio of the material, the ball and the water is 1:7:1, and then pre-calcining at a temperature of 800°C for 2 hours in an air atmosphere to obtain a pre-calcined material;

[0065] (2) Mix the remaining additives and the obtained pre-burnt material, and perform secondary sand grinding for 2 hours. During the process, the mass ratio of the material, the ball and the water is 1:7:1, and the average particle size of the sand milled material is 1.2 μm. Then mix the dried powder after the secondary sand grinding with 10 wt% of PVA for granulation and molding, and finally sintering. The sintering includes a 1310°C insulation section for 150 minutes and a cooling section. The oxygen content in the insulation section is 5 vol%. In the cooling section, the oxygen content at 1250°C is 3.5 vol%, the oxygen content at 1200°C is 3 vol%, and the oxygen content at 1150°C is 1.6 vol%. The manganese-zinc power ferrite material is obtained.

[0066] Example 4

[0067] The present embodiment provides a manganese-zinc power ferrite material, which consists of a main component and an additive, wherein the main component is 52.2 mol% Fe2O3 and 10 mol% ZnO, and the rest is MnO; the additive is 1500 ppm SnO2, 700 ppm CaCO3, 250 ppm Nb2O5 and 200 ppm ZrO2, based on the total mass of the main component.

[0068] The preparation method of the manganese-zinc power ferrite material comprises:

[0069] (1) mixing the main component and SnO2, and performing a sand milling for 3 hours, during which the mass ratio of the material, the ball and the water is 1:6:1.5, and then pre-calcining at a temperature of 750°C for 3 hours in an air atmosphere to obtain a pre-calcined material;

[0070] (2) Mix the remaining additives and the obtained pre-burned material, and perform secondary sand grinding for 3 hours. During the process, the mass ratio of the material, the ball and the water is 1:6:1.5, and the average particle size of the sand abrasive is 1 μm. Then 8 wt% of PVA is mixed for granulation and molding, and finally sintering is performed. The sintering includes a 1300°C insulation section for 200 minutes and a cooling section. The oxygen content in the insulation section is 5 vol%. In the cooling section, the oxygen content at 1250°C is 3.5 vol%, the oxygen content at 1200°C is 3 vol%, and the oxygen content at 1150°C is 1.8 vol%. The manganese-zinc power ferrite material is obtained.

[0071] Example 5

[0072] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof, which is different from Embodiment 1 in that the amount of Fe2O3 accounts for 51.5 mol%.

[0073] Example 6

[0074] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof, which is different from Embodiment 1 in that the amount of ZnO accounts for 8 mol%.

[0075] Example 7

[0076] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof, which is different from Embodiment 1 in that the mass of SnO2 is 800 ppm of the total mass of the main component.

[0077] Example 8

[0078] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof, which is different from Embodiment 1 in that the mass of SnO2 is 2200 ppm of the total mass of the main component.

[0079] Example 9

[0080] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof, which differs from Embodiment 1 in that the mass of CaCO3 is 400 ppm of the total mass of the main component.

[0081] Example 10

[0082] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof, which differs from Embodiment 1 in that the mass of CaCO3 is 1200 ppm of the total mass of the main component.

[0083] Embodiment 11

[0084] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof, which differs from Embodiment 1 in that the mass of Nb2O5 is 80 ppm of the total mass of the main component.

[0085] Example 12

[0086] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof, which differs from Embodiment 1 in that the mass of Nb2O5 is 350 ppm of the total mass of the main component.

[0087] Embodiment 13

[0088] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof, which is different from Embodiment 1 in that the mass of ZrO2 is 80 ppm of the total mass of the main component.

[0089] Embodiment 14

[0090] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof, which is different from Embodiment 1 in that the mass of ZrO2 is 350 ppm of the total mass of the main component.

[0091] Embodiment 15

[0092] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The difference from Embodiment 1 is that in the preparation method, SnO2 is not mixed in step (1), but is mixed with other additives in step (2).

[0093] Example 16

[0094] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The difference from Embodiment 1 is that in the cooling stage in step (2), when the temperature drops to 1250°C, the oxygen content is controlled at 1.5 vol%, at 1200°C, the oxygen content is controlled at 1 vol%, and at 1150°C, the oxygen content is controlled at 0.5 vol%.

[0095] Comparative Example 1

[0096] This comparative example provides a manganese-zinc power ferrite material and a preparation method thereof, which differs from Example 1 in that SnO2 is not added.

[0097] Comparative Example 2

[0098] This comparative example provides a manganese-zinc power ferrite material and a preparation method thereof, which differs from Example 1 in that CaCO3 is not added.

[0099] Comparative Example 3

[0100] This comparative example provides a manganese-zinc power ferrite material and a preparation method thereof, which differs from Example 1 in that Nb2O5 is not added.

[0101] Comparative Example 4

[0102] This comparative example provides a manganese-zinc power ferrite material and a preparation method thereof, which differs from Example 1 in that ZrO2 is not added.

[0103] The manganese-zinc power ferrite material obtained above was placed on a SY8219 test device, and its loss was tested under the conditions of 100kHz 200mT, T=140℃ / 150℃ / 160℃. The loss results are shown in Table 1.

[0104] Table 1

[0105]

[0106]

[0107] In summary, the present invention controls the power consumption valley point near the operating temperature through a suitable main formula ratio, and then fine-tunes the power consumption valley point of the material and reduces the power consumption through a suitable additive, so as to achieve the ultra-high temperature (140-160°C) and low loss (power consumption P under the conditions of 100kHz and 200mT) of the manganese-zinc power ferrite material. cv ≤340kW / m 3 ) performance.

[0108] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A manganese-zinc power ferrite material, characterized in that: The manganese-zinc power ferrite material includes a main component and an additive, wherein the main component includes Fe2O3, ZnO and MnO; and the additive includes SnO2, CaCO3, Nb2O5 and ZrO2.

2. The manganese-zinc power ferrite material according to claim 1, characterized in that: Taking the total amount of the main components as 100 mol%, the main components include: Fe2O3 52~52.5mol% ZnO 9~11mol% MnO balance.

3. The manganese-zinc power ferrite material according to claim 1 or 2, characterized in that: The mass of SnO2 is 1000-2000ppm of the total mass of the main component; Preferably, the mass of the CaCO3 is 500 to 1000 ppm of the total mass of the main component; Preferably, the mass of the Nb2O5 is 100 to 300 ppm of the total mass of the main component; Preferably, the mass of the ZrO2 is 100 to 300 ppm of the total mass of the main component.

4. A method for preparing the manganese-zinc power ferrite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: (1) mixing the main component and SnO2, performing a sand grinding and then pre-burning to obtain a pre-burned material; (2) mixing the remaining additives with the obtained pre-burnt material, performing secondary sand grinding and then sintering to obtain the manganese-zinc power ferrite material.

5. The preparation method according to claim 4, characterized in that: In the first sand milling process described in step (1), the mass ratio of material, ball and water is 1:(5-7):(1-2); Preferably, the time of the first sanding in step (1) is 2 to 4 hours; Preferably, the pre-burning temperature in step (1) is 700-800°C; Preferably, the pre-burning time in step (1) is 2 to 4 hours; Preferably, the pre-firing atmosphere in step (1) is an air atmosphere.

6. The preparation method according to claim 4 or 5, characterized in that: During the secondary sand milling process of step (2), the mass ratio of material, ball and water is 1:(5-7):(1-2); Preferably, the secondary sanding time in step (2) is 2 to 4 hours; Preferably, the average particle size of the sanding material obtained after the secondary sanding in step (2) is 0.9 to 1.2 μm.

7. The preparation method according to any one of claims 4 to 6, characterized in that: Step (2) further includes granulation and molding after the secondary sand grinding; Preferably, the granulation material is added during the granulation process; Preferably, the granulation material comprises PVA and / or PVB; Preferably, the mass of the granulated material is 5-10wt% of the mass of the dried powder after secondary sand grinding.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The sintering in step (2) includes a heat preservation section and a temperature reduction section; Preferably, the insulation period is 150 to 250 minutes; Preferably, the temperature of the insulation section is 1280-1310°C.

9. The preparation method according to claim 8, characterized in that: The oxygen content in the cooling section at 1250°C is 3-4 vol%; Preferably, the oxygen content in the cooling section at 1200° C. is 2.5 to 3.5 vol%; Preferably, the oxygen content in the temperature reduction section at 1150° C. is 1-2 vol%.

10. An application of the manganese-zinc power ferrite material according to any one of claims 1 to 3, characterized in that: The manganese-zinc power ferrite material is used for electronic devices.

Citation Information

Patent Citations

  • High temperature and low loss MnZn ferrite core and preparation method thereof

    CN102219486A

  • Preparation method of high-temperature, high-frequency and low-loss ferrite material

    CN112125655A

  • High-temperature low-loss MnZn power ferrite and preparation method thereof

    CN113956028A